2015
DOI: 10.1016/j.landurbplan.2014.10.006
|View full text |Cite
|
Sign up to set email alerts
|

How do amenity migrants learn to be environmental stewards of rural landscapes?

Abstract: The changing socio-ecological dynamics in rural landscapes associated with amenity migration in post-industrial nations such as Australia has implications for environmental management.The number of non-farming landholders now occupying regions once valued primarily for agriculture has increased rapidly in the past decade, with property turnover rates in some rural Australian regions as high as 50 percent. Given amenity migrants can shape rural ecologies through land management practice, it is vital that we und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 55 publications
(74 reference statements)
1
29
0
1
Order By: Relevance
“…Other research projects (e.g. Cooke and Lane, 2015) have, however, demonstrated migration to new and unfamiliar places. In our study, this attribute could take the following two levels: 'I have lived in this area for a short or long period of my life' and 'I have never lived in this area before'.…”
Section: (Insert Here Table 1)mentioning
confidence: 99%
“…Other research projects (e.g. Cooke and Lane, 2015) have, however, demonstrated migration to new and unfamiliar places. In our study, this attribute could take the following two levels: 'I have lived in this area for a short or long period of my life' and 'I have never lived in this area before'.…”
Section: (Insert Here Table 1)mentioning
confidence: 99%
“…However, weed management social science shows that knowledge and communication are not necessarily the most significant or only influences on weed management (Head, 2017). As well as economic factors, practice is influenced by a range of social and cultural factors including social norms (Ma et al, 2018;McKiernan, 2017), trust (Graham, 2014), divergent views about plant belonging that do not neatly accord to the native/non-native distinction (Cooke and Lane, 2015), and pragmatic decisions about living with and tolerating weeds in various ways .…”
Section: Weed Hygiene Researchmentioning
confidence: 99%
“…Understanding the nuances of this message can be challenging for new migrants to fire prone areas. Cooke and Lane report that, on finding that their understanding of ecological processes and land management ‘informed by prior urban lifestyles’ has limited relevance in rural contexts, many landholders ‘turn to experiential learning’ (Cooke and Lane, 2015: 43). Most of this learning takes place on property, and is dependent on observation of biophysical responses to human actions (2015: 48).…”
Section: Unbounding Firementioning
confidence: 99%
“…Moreover, the ways in which these people learn about land and fire management frequently differ, at least initially, from those of long-term inhabitants in rural areas. It has been suggested that these differences in learning styles are due, at least in part, to the ‘property centric’ (Cooke and Lane, 2015: 46) orientation of relative newcomers which contrasts with the more social positioning of long-term farmers who have a ‘collective interest in maintaining productive rural landscapes’ (2015: 49, see also Eriksen and Prior, 2011).…”
Section: Introductionmentioning
confidence: 99%